Development Strategy and Investment Criteria: Complementary or Competitive? - King, Timothy (Quarterly Journal of Economics, 1966)
Introduction, 108. — I. The three approaches and the issues facing them, 109. — II. Similar objectives will require different policies, 114. — III. Contrast between development strategy and benefit-cost analysis, 117. — IV. Conclusion, 119.